Siwalik basin of Arunachal Himalaya, India: a case study (Journal of Nepal Geological Society, 1998)
The Siwalik basin of Arunachal Himalaya is a part of the Himalayan foreland. Due to continental collision between Indian and Eurasian plates, the Himalayan mountain system experienced intense uplift and erosion and as a result, a large amount of siliciclastic sediments accumulated within the foreland and a remnant ocean basin (which was commonly known as foredeep) was developed during Eocene. Moreover, the sediments were deposited by a large river draining the uplifted Himalayan belt during late Neogene. From the pattern of lithofacies, the river may be envisaged as braided type and was a bit shallow relative to its width, floored by bars and channels of low sinuosity and with a bed load of sand and pebbly sediments.These sediments present in the Arunachal foothills are bounded by the Brahmaputra Alluviums in the south and the Gondwana belt in the north and, by a system of frontal faults and the Main Boundary Fault, respectively. The sediments are mostly of molasse type (Upper Tertiary sediments), of different sedimentary facies present in the form of thick accumulation of multilateral and multistoried bodies. Moreover, the depositional basin suffered from some tectonic disturbances for which open folds and many reverse faults were formed.With the formation of foredeep infront of the Himalaya, a reversal of slope towards north-west took place in post-Barail times and during the later part of the Tertiary, the Himalayan and the Upper Assam basin were continuous below the Brahmaputra Alluviums as evidenced by field and laboratory observations.From these observations, it is seen that the Siwalik basin of Arunachal Himalaya has close resemblance with the Tertiary basin (Neogene basin) of Upper Assam rather than the Siwalik basin of western Himalaya and thus, this basin may be treated as a separate basin which may be renamed as "Tertiary basin of Arunachsl".